Neglected tracheo-bronchial foreign bodies in adults - Dar, Khurshid Ahmad; Dar, Nisar Hussain; Mehfooz, Nazia; Datta, B. S. (International Journal of Research in Medical Sciences, 2017)
Background: Neglected tracheobronchial foreign body in adults is quite rare in clinical practice. The present paper describes our experience of four adult patients who had chronic chest Symptoms (Cough, Chest Discomfort recurrent pneumonia) caused by foreign body inhalation, undetected for 3 months -15 years. Methods: This was a short retrospective study. Four adult patients with neglected trachaeobronchial foreign bodies which were removed in our medical college in the past 1 year were included in this short study. Case sheets were scrutinized for clinical features, X-ray findings, CT findings and bronchoscopic findings. Results: The diagnosis of foreign body was made by radiology (X-ray + CT) in 3 patients and FOB in one patient. In all 4 patients foreign body was removed by fiber optic bronchospocopy. Endo bronchial electrocautery was used in one patient to cut the web above the FB. Foreign bodies removed were whistle top, end of IV cannula, scarf pin and maize corn. Conclusions: Study concludes that chronic, unexplained respiratory complaints should warrant further investigations to exclude foreign body and despite no history of Foreign Body and normal X-Ray, early diagnosis and intervention would avoid complications.